PERAN PENDIDIKAN KRISTIANI DALAM PENGUATAN KARAKTER KRISTIANI KELUARGA DI ABAD 21: Perbubahan, Teknologi, Pendidikan Kristiani, Keluarga - Maria Sinta Sembiring (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2024)
In the 21st century, humans live in an age of constant change. The changes that occur are inseparable from the development of increasingly sophisticated technology. Nowadays, all about the human life movement has become digital technology. Digital technology has a huge influence on humans and Christian families today are no exception. The advancement of digital technology is inevitable. Technology brings enormous changes to the behavior, spirituality, and truth values held by humans. Now, the value of ultimate truth is getting harder to apply. What is right and what is wrong depend on the situation. The Word of God is no longer an absolute truth to be practiced in this era, even there has an assumption that the principles of Christian life are no longer contextualized in this era. This situation illustrates that in the 21st century, the character of faithfulness to the truth of God's Word is eroding and deserves to be questioned, especially in the lives of today's youth. For this reason, Christian education is very important to be instilled in the family, so that Christian families are able to shape the character of life that is faithful to biblical truth.